2007
DOI: 10.1111/j.1540-8167.2007.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison Between Open Irrigation Technology and Intracardiac‐Echo‐Guided Energy Delivery for Pulmonary Vein Antrum Isolation: Procedural Parameters, Outcomes, and the Effect on Esophageal Injury

Abstract: Although both OIT and ICE-guided energy delivery possess a similar effect in treating AF, OIT seems to be superior in terms of achieving isolation and shortening fluoroscopy exposure. Moreover, a lower incidence of esophageal wall injury was observed utilizing OIT for PVAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
3
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 37 publications
5
83
3
4
Order By: Relevance
“…6 In fact, development of esophageal ulcerations has been found to be dependent on the RFCA lesion set as well as the maximum energy delivered at the posterior left atrial wall. 7 Also, some authors believe that esophageal ulceration can be a potential precursor of a dramatic life-threatening condition, the atrio-esophageal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…6 In fact, development of esophageal ulcerations has been found to be dependent on the RFCA lesion set as well as the maximum energy delivered at the posterior left atrial wall. 7 Also, some authors believe that esophageal ulceration can be a potential precursor of a dramatic life-threatening condition, the atrio-esophageal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…insertion depth of the electrode into the tissue) [Tungjitkusolmun et al 2001], and blood flow on electrode and cardiac surface [Cao et al 2001]. The effect of different electrode designs [Marrouche et al 2007] or even different energy sources [Aupperle et al 2005] could also be considered.…”
Section: )mentioning
confidence: 99%
“…This question is essential, since two recent experimental studies demonstrated severe cases of thermal injury in the esophagus muscular layer during RF cardiac ablation [Aupperle et al 2005, Marrouche et al 2007]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopy (and TEE) should be avoided as instrumentation of the esophagus may cause rapid deterioration and even death, as noted in previous surgical cases (26,27). Sensitivity of a barium swallow is low for detection of fistulas therefore the best (34,35), introduction of open irrigated systems for ablation (28), esophageal cooling with water-irrigated intraesophageal balloon during the ablation (36), using pain as an indicator of temperature rise in the esophagus (37).…”
Section: Atrioesophageal Fistula As a Complication Of Ablation Proceduresmentioning
confidence: 99%